Nitrogen-doped graphene interpenetrated 3D Ni-nanocages: efficient and stable water-to-dioxygen electrocatalysts - Dhavale, Vishal M.; Gaikwad, Sachin S.; George, Leena; Devi, R. Nandini; Kurungot, Sreekumar (Nanoscale, 2014)
Herein, we report the synthesis of a nitrogen-doped graphene (NGr) interpenetrated 3D Ni-nanocage (Ni-NGr) electrocatalyst by a simple water-in-oil (w/o) emulsion technique for oxidation of water to dioxygen. Correlation of adsorption of NGr and subsequent interpenetration through the specific surface plane of nickel particles as well as the concomitant interaction of N and C with Ni in the nano-regime has been investigated. Apart from the benefits of the synergistic interactions between Ni, N, and C, the overall integrity of the structure and its intra-molecular connectivity within the framework help in achieving better oxygen evolution characteristics at a significantly reduced overpotential. The engineered Ni-NGr nanocage displays a substantially low overpotential of similar to 290 mV at a practical current density of 20 mA cm(-2) in 0.1 M KOH. In comparison, NGr and Ni-particles as separate entities give overpotentials of similar to 570 and similar to 370 mV under similar conditions. Moreover, the long term stability of Ni-NGr was investigated by anodic potential cycling for 500 cycles and an 8.5% increment in the overpotential at 20 mA cm(-2) was observed. Additionally, a chronoamperometric test was performed for 15 h at 20 mA cm(-2), which highlights the better sustainability of Ni-NGr under the actual operating conditions. Finally, the quantitative estimation of evolved oxygen was monitored by gas chromatography and was found to be 70 mmol h(-1) g(-1) of oxygen, which is constant in the second cycle as well.